PENGOLAHAN MOTIF TERINSPIRASI DARI KAIN BATIK GENDONGAN LIONG UNTUK PENGEMBANGAN PRODUK GENDONGAN MEI TAI - Agtha Juliani Purnama Dewi; Morinta Rosandini (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2021)
Liong sling batik cloth has decreased interest because it is considered ancient and cause aches or pain in the shoulder when used. Today's parents prefer to use a modern baby carrier like Mei Tai whose use rests on two shoulders to minimize aches or pain in the shoulder, but in Indonesia, the current mei tai baby carrier products still use general motifs such as cartoons or geometric fields and do not contain cultural elements. The research method used in this study is a qualitative research method that conducts in-depth analysis and quantitative methods that aim to coordinate data such as literature studies, observations, interviews with Certified Babywearing Consultants, and conduct research by developing motifs on Liong sling batik fabric. The final result of this research is the visualization of product merchandise which contains a little information about the structure and the meaning of the Liong sling batik motif so that it can be known by the public. Then there are processed motifs inspired by Liong sling batik fabric with more modern compositions and shapes, and the creation of Mei Tai's baby carrier products, which adopted designs for developing motifs inspired by more modern Liong batik.